FAKTOR YANG MEMPENGARUHI KINERJA GURU SMP NEGERI TERAKREDITASI A DI KOTA BATAM - Pulung Peranginangin; Brigitta Neti Iswantari (Universitas Lambung Mangkurat, 2021)
The purpose of the research is to know the influences of knowledge sharing, self motivation, training and development towards teachers’ working performance in public middle school accredited A in Batam Kota. This research is conducted in SMPN 6 Batam, SMPN 10 Batam, SMPN 12 Batam, SMPN 28 Batam, SMPN 31 Batam and SMPN 42 Batam.The sample taken has been done by quota sampling method. The number of questionnaire used in the research is 186 to answer three proposed hypothesis. The method uses is multiple regression. The result of the research showed that knowledge sharing, self motivation, training dan development have an influence towards teachers’ performance in Public Junior High Schools accredited A in Batam Kota.